Sustainable concrete solutions - Georgopoulos, Costas (Chichester, West Sussex : John Wiley & Sons Inc., 2014)
'The book will provide students with a thorough evaluation of the advantages and disadvantages of concrete a sustainable building material'--
Machine generated contents note: Preface Foreword Professor Jacqui Glass Chair in Architecture and Sustainable Construction, Loughborough University 1. Introduction 1.1 Sustainability and Sustainable Development 1.2 The Role of the Design Team in Sustainable Development 1.3 Sustainability Credentials of Concrete 1.4 Book Layout and Context 2. Challenges & Responses 2.1 Introduction 2.2 Climate Change 2.3 Environmental Protection 2.4 Social Progress 2.5 Economic Growth 2.6 Regulatory Responses 2.7 Summary 3. Conceptual Design of Buildings & Infrastructure 3.1 Introduction 3.2 Conceptual Design of Buildings 3.3 Conceptual Design of Infrastructure 3.4 Summary 4. Material Specification 4.1 Introduction 4.2 Assessing Environmental Impacts of Materials 4.3 Responsible Sourcing of Materials 4.4 Cements and Combinations 4.5 Aggregates 4.6 Water 4.7 Admixtures 4.8 Novel Constituents 4.9 Reinforcement 4.10 Special Concretes 4.11 Specification Examples 4.12 Summary 5. Construction, Operation and End of Life 5.1 Construction 5.2 Operation 5.3 End of Life 5.4 Summary Appendix A: Thermal Mass Appendix B: Biomass Product Appendix C: Choice of Concrete Slab Options Appendix D: Worked Example on Embodied CO2 for a Building Slab Index .
Includes bibliographical references and index.
Keywords: Concrete construction -- Environmental aspects; Sustainable buildings